Connectivity alterations underlying the breakdown of pseudoneglect: New insights from healthy and pathological aging - Bagattini, Chiara; Esposito, Marco; Ferrari, Clarissa; Mazza, Veronica; Brignani, Debora (Frontiers in Aging Neuroscience, 2022)
A right-hemisphere dominance for visuospatial attention has been invoked as the most prominent neural feature of pseudoneglect (i.e., the leftward visuospatial bias exhibited in neurologically healthy individuals) but the neurophysiological underpinning of such advantage are still controversial. Previous studies investigating visuospatial bias in multiple-objects visual enumeration reported that pseudoneglect is maintained in healthy elderly and in amnesic Mild Cognitive Impairment (aMCI), but not in Alzheimer’s disease (AD). In the present study, we aimed at investigating the neurophysiological correlates sustaining the rearrangements of the visuospatial bias along the progression from normal to pathological aging. To this aim, we recorded EEG activity during an enumeration task and analyzed intra-hemispheric fronto-parietal and inter-hemispheric effective connectivity adopting indexes from graph theory in mild AD patients, aMCI patients and healthy elderly controls (HC). Results revealed that HC showed the leftward bias and stronger fronto-parietal effective connectivity in the right as compared to the left hemisphere. A breakdown of pseudoneglect in AD patients was associated with both the loss of the fronto-parietal asymmetry and the reduction of inter-hemispheric parietal interactions. In aMCI initial alterations of the attentional bias were associated to a reduction of parietal inter-hemispheric communication, but not with modulations of the right fronto-parietal connectivity advantage, that remained intact. These data provide support to the involvement of fronto-parietal and inter-parietal pathways in the leftward spatial bias, extending these notions to the complex neurophysiological alterations characterizing pathological aging.